Health-Related Social Needs Facing Youth With Nonalcoholic Fatty Liver Disease. Issue 1 (10th February 2022) - Orkin, Sarah; Yodoshi, Toshifumi; Sun, Qin; Fei, Lin; Meryum, Syeda; Ley, Sanita; Arce-Clachar, Ana Catalina; Bramlage, Kristin; Xanthakos, Stavra; Kahn, Robert; Beck, Andrew F.; Mouzaki, Marialena
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The objective of this study was to identify the prevalence of health-related social needs among youth with nonalcoholic fatty liver disease. Methods: Retrospective review of prospectively administered health-related social needs questionnaires from Steatohepatitis Clinics. Results: Patients with nonalcoholic fatty liver disease (n = 271) were predominantly male (72%) and non-Hispanic (68%). The most common unmet need was food insecurity (13%, n = 36). Families who endorsed food insecurity at the first visit were 27-fold more likely to have unmet health-related social needs persist at subsequent visits than those who were food secure at their first visit (95% confidence interval, 6.7-111). Conclusions: Screening for social, economic, and environmental needs may identify previously unrecognized family challenges and may enhance intervention delivery, inform resource allocation, and improve outcomes.